Practice-based perspectives on multimodal documents: Corpora vs connoisseurship. (December 2017) - Waller, Robert
Abstract: Multimodal studies are essentially interdisciplinary, crossing boundaries between the verbal and the visual, between creation and consumption, and, it is argued here, between academic analysis and professional practices. This paper presents a practice-based perspective on multimodal document genres which feature typography and page/screen layout. It is argued that in order to reliably account for observed data, analysts need to distinguish between effects which represent an effort to create meaning, those which are by-products of production technology, and those which are intended as navigational support for users. A range of problems is identified, facing those who seek to classify multimodal genres, including problems of method, interdisciplinarity, naming, granularity, and exemplification. Additional problems particular to the study of real documents include design competence, dysfunctional genres, creativity and continuous technical change. Insights from design practice are discussed, introducing a pattern language approach to develop a level of connoisseurship and good judgement that complements the more formal analysis represented by corpus studies and taxonomy.